Ecological connectivity research in urban areas - LaPoint, Scott; Balkenhol, Niko; Hale, James; Sadler, Jonathan; van der Ree, Rodney (Functional ecology, 2015)
Summary The successful movement of individuals is fundamental to life. Facilitating these movements by promoting ecological connectivity has become a central theme in ecology and conservation. Urban areas contain more than half of the world's human population, and their potential to support biodiversity and to connect their citizens to nature is increasingly recognized. Promoting ecological connectivity within these areas is essential to reaching this potential. However, our current understanding of ecological connectivity within urban areas appears limited. We reviewed the published scientific literature to assess the state‐of‐the‐art of ecological connectivity research in urban areas, summarized trends in study attributes and highlighted knowledge gaps. We found 174 papers that investigated ecological connectivity within urban areas. These papers addressed either structural (48) or functional connectivity (111), and some addressed both (15), but contained substantial geographic and taxonomic biases. These papers rarely defined the aspect of connectivity they were investigating and objective descriptions of the local urban context were uncommon. Formulated hypotheses or a priori predictions were typically unstated and many papers used suboptimal study designs and methods. We suggest future studies explicitly consider and quantify the landscape within their analyses and make greater use of available and rapidly developing tools and methods for measuring functional connectivity (e.g. biotelemetry or landscape genetics). We also highlight the need for studies to clearly define how the terms ‘urban’ and ‘connectivity’ have been applied. Knowledge gaps in ecological connectivity in urban areas remain, partly because the field is still in its infancy and partly because we must better capitalize on the state‐of‐the‐art technological and analytical techniques that are increasingly available. Well‐designed studies that employed high‐resolution data and powerful analytical techniques highlight our abilities to quantify ecological connectivity in urban areas. These studies are exemplary, setting the standards for future research to facilitate data‐driven and evidence‐based biodiversity‐friendly infrastructure planning in urban areas. Lay Summary